Protective effect of short-chain fructo-oligosaccharides from chicory on alcohol-induced injury in GES-1 cells via Keap1/Nrf2 and NLRP3 inflammasome signaling pathways - Chen, Yan; Zhao, Yanan; Lu, Hao; Zhang, Weichen; Gai, Yanan; Niu, Guanting; Meng, Xiuhua; Lv, Han; Qian, Xiaoguo; Ding, Xiaoqin; Chen, Jian (Frontiers in Nutrition, 2024)
Numerous studies have demonstrated that polysaccharides derived from chicory possess the ability to regulate host signaling and modify mucosal damage. Yet, the effect and mechanism of short-chain fructo-oligosaccharides (scFOS) on gastric mucosa remain unclear. Hence, the protective effect of three scFOS (1-Kestose, Nystose, and 1F-Fructofuranosylnystose) against ethanol-induced injury in gastric epithelial (GES-1) cells, and the underlying molecular mechanism involved was investigated in this study. Treatment with 7% ethanol decreased the cell viability of GES-1 cells, resulting in oxidative stress and inflammation. However, pretreatment with scFOS exhibited significant improvements in cell viability, and mitigated oxidative stress and inflammation. scFOS markedly elevated the protein expression of Nrf2, HO-1, SOD1, and SOD2, while suppressing the expression of Keap1. scFOS pretreatment could also maintain mitochondrial membrane potential balance and reduce apoptosis. In addition, scFOS was observed to reduce the protein level of NLRP3, Caspase-1 and ASC. In conclusion, scFOS served a preventive function in mitigating oxidative stress and inflammation in ethanol-exposed GES-1 cells through modulation of the Keap1/Nrf2 and NLRP3 inflammasome signaling pathways. Collectively, the results indicated that scFOS could significantly mitigate ethanol-induced gastric cell damage, suggesting its potential for safeguarding gastrointestinal health.